Mangrove Planting as an Effort to Prevent Abrasion on The Coast of The Pulau Ketam Kuala Perlis Forest Reserve - Syawal Harahap, Fitra; Walida, Hilwa; Harahap, Arman; Pane , Rahmadani; Bangun, Budianto; Nasution, Agustina; Rauf, Abdul; Sarifuddin, Sarifuddin; Panjaitan, Bernat (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Abrasion can cause environmental damage, damage coastal infrastructure, and threaten the lives of communities living around the coast. One effort that can be made to prevent abrasion is planting mangroves along the coastal area. Mangrove forests are important habitats for marine organisms and act as coastal guards against abrasion. One area that has mangrove forests and is quite vulnerable to abrasion is Pulau Ketam Kuala Perlis. This activity aims to increase community awareness about the importance of mangroves in preventing abrasion, specifically in Pulau Ketam Kuala Perlis. The methods used include observation, interviews, and planting. The results of the Community Service Activity show that the community of understands and greatly benefits from mangrove planting efforts and abrasion prevention.